Comparison of NB‐UVB combination therapy regimens for vitiligo: A systematic review and network meta‐analysis. (1st December 2022) - Zhu, Baohua; Liu, Chengjiang; Zhang, Lan; Wang, Jun; Chen, Mingling; Wei, Yuegang
Abstract: Background: Vitiligo was an autoimmune disease and some guidelines for the management of vitiligo encouraged the use of NB‐UVB combination therapies to enhance repigmentation. Objectives: To compare the effectiveness of current NB‐UVB combination regimen at the improvement in repigmentation through a systematic review and network meta‐analysis. Methods: We searched the electronic databases for randomized controlled trials related to NB‐UVB combination therapy for vitiligo till October 2022. STATA15.0 software was applied to carrying out data analysis. Results: A total of 28 eligible studies involving 1194 participants were enrolled in the analysis. The NMA results revealed that compared with NB‐UVB, carboxytherapy [OR = 32.35, 95% CI (1.79, 586.05)], Er: YAG laser+ topical 5% 5‐FU [OR = 10.74, 95% CI (4.05, 28.49)], needling/micro‐needling [OR = 3.42, 95% CI (1.18, 9.88)], betamethasone intramuscular injection [OR = 3.08, 95% CI (1.17, 8.13)], topical tacrolimus [OR = 2.54, 95% CI (1.30, 4.94)], and oral Chinese herbal medicine compound [OR = 2.51, 95% CI (1.40, 4.50)] integrated with NB‐UVB were more efficacious in excellent to complete repigmentation response rate (≥75%). Besides, NB‐UVB+ Er: YAG laser+ topical 5% 5‐FU [OR = 0.17, 95% CI (0.04, 0.67)] and NB‐UVB+ needling/micro‐needling [OR = 0.24, 95% CI (0.06, 0.88)] were less likely evaluated as ineffective repigmentation response (≤25%). Conclusions: All combination therapies ranked higher than NB‐UVB monotherapy in inducing successful repigmentation and avoiding failed treatment in patients with vitiligo. Comprehensive consideration, NB‐UVB+ Er: YAG laser+ topical 5% 5‐FU and NB‐UVB+ needling/microneedling would be the preferred therapeutic approaches.